Bridging tradition and modernity: exploring patutan (the modal system) in Balinese music through the hybrid composition ‘cane’ - Kartawan, I Made; Putra, I Made Dwi Andika; Hartini, Ni Putu (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2024)
This paper examines how the composer integrates traditional Balinese gamelan elements with Western musical concepts in the creation of the piece